An integrated approach with experimental and computational tools outlining the cooperative binding between 2-phenylchromone and human serum albumin - Caruso, Ícaro Putinhon [UNESP]; Filho, José Maria Barbosa; De Araújo, Alexandre Suman [UNESP]; De Souza, Fátima Pereira [UNESP]; Fossey, Marcelo Andrés [UNESP]; Cornélio, Marinônio Lopes [UNESP] (Elsevier, 2016)
2-Phenylchromone (2PHE) is a flavone, found in cereals and herbs, indispensable in the human diet. Its chemical structure is the basis of all flavonoids present in black and green tea, soybean, red fruits and so on. Although offering such nutritional value, it still requires a molecular approach to understand its interactions with a specific target. The combination of experimental and computational techniques makes it possible to describe the interaction between 2PHE and human serum albumin (HSA). Fluorescence spectroscopy results show that the quenching mechanism is static, and thermodynamic analysis points to an entropically driven complex. The binding density function method provides information about a positive cooperative interaction, while drug displacement experiments indicate Sites 1 and 2 of HSA as the most probable binding sites. From the molecular dynamic study, it appears that the molecular docking is in agreement with experimental data and thus more realistic.
Keywords: 2-Phenylchromone; Binding density function; Computational methods; Cooperative binding; Fluorescence spectroscopy; Human serum albumin